Cerdas Mengenal Obat Bersama Apoteker Cilik (Apocil) di SDN 1 Jepang Kudus - Rakhmi Hidayati; Annis Rahmawaty; David Laksanama Caesar (Muria Jurnal Layanan Masyarakat, 2022)
The pharmacist profession in Indonesia as one of the health workers responsible for pharmaceutical work is still many who do not know, one of the efforts to introduce the pharmacist profession as a health worker who has expertise in the field of medicine in the community is the little pharmacist program. The purpose of this activity is so that children can get to know medicines from an early age and foster interest in children from an early age. This activity has been carried out at SD Negeri 1 Jepang Kudus with a total of 30 participants from grade 5 elementary school students. The method of implementing this activity begins with the guidance of 3 students who were selected as child pharmacists for 1 week related to material on various drugs, how to grind drugs and wrap the puyer properly and correctly. In the implementation, the little pharmacists delivered education to the participants. This activity became more interesting because at the end of the activity there was a puyer wrapping competition and the selection of the best little pharmacist.